2021
DOI: 10.3390/cancers13030425
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine and Folate Metabolism Are Targetable Vulnerabilities of Metastatic Colorectal Cancer

Abstract: With most cancer-related deaths resulting from metastasis, the development of new therapeutic approaches against metastatic colorectal cancer (mCRC) is essential to increasing patient survival. The metabolic adaptations that support mCRC remain undefined and their elucidation is crucial to identify potential therapeutic targets. Here, we employed a strategy for the rational identification of targetable metabolic vulnerabilities. This strategy involved first a thorough metabolic characterisation of same-patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Dysregulated metabolism plays a vital role in cancer cell progression and metastasis [22,23,25,26,4549]. In this study, we have shown that TNBC cell lines differentiating in their metastatic potential in vivo exhibit different metabolic profile already in vitro, and those differences are independent of the abundance of canonical EMT markers.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Dysregulated metabolism plays a vital role in cancer cell progression and metastasis [22,23,25,26,4549]. In this study, we have shown that TNBC cell lines differentiating in their metastatic potential in vivo exhibit different metabolic profile already in vitro, and those differences are independent of the abundance of canonical EMT markers.…”
Section: Discussionmentioning
confidence: 59%
“…Nevertheless, we found increased level of citrate and molecules involved in citrate metabolism, which could suggest higher glucose contribution to TCA cycle in HMP cell lines. The greater flux of glucose into TCA cycle was recently reported in metastatic colorectal cancer cell lines [49]. The enhanced glycolysis along with intracellular accumulation of citrate were shown to enhance TNBC cell invasion and metastasis via AKT/ERK signaling pathway [46].…”
Section: Discussionmentioning
confidence: 94%
“…Transcriptomics and measured rates of metabolite uptake and secretions were integrated to the reconstructions using GIM 3 E [14] . GIM 3 E uses flux minimization weighted by transcriptomics Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Case in point, a GSMM analysis of two isogenic prostate cancer cell lines identified that the cancer cell lines with cancer stem cell like phenotype were vulnerable to the accumulation of long-chain fatty acids with antiproliferative effects and could be selectively killed by blocking fatty acid oxidation [13] . Likewise, in a same patient-derived cell line panel, GSMMs have also enabled the identification that the combined inhibition of cystine uptake and folate metabolism is highly selective against metastatic cells [14] .…”
Section: Introductionmentioning
confidence: 99%
“…The first synthetic MTHFD1/2 inhibitor LY345899 has shown its anti-tumor activity in CRC [295]. Treatment of LY345899 led to reduced proliferative rate in primary CRC cells (SW480), its lymph node metastasis (SW620) and a liver metastatic derivative (SW620-LiM2), while no toxicity in the normal colon epithelial cells was observed [296]. In line with this, Ju et al found that LY345899 inhibited tumor growth and decreased the tumor weight in CRC patient-derived xenograft models without acute or delayed toxicity [297].…”
Section: Targeting One-carbon Metabolismmentioning
confidence: 99%